The Influence of Social Media Influencers and Café Atmosphere on Purchase Decision at Café T1311 Medan - Chen, Michael; Dedy Lazuardi (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2023)
The primary objective of this study is to investigate how social media influencers and the ambiance of Café T1311 Medan impact customers' purchasing decisions. This research falls under the category of quantitative research. The research population comprised Café T1311 Medan customers, and a sample of 100 respondents was chosen using accidental sampling methods. Data collection involved the use of questionnaires, interviews, and the examination of relevant documents. Subsequently, the collected data was processed and analyzed using multiple linear regression analysis. The findings demonstrated that both Social Media Influencers (X1) and Café Atmosphere (X2) had a positive and significant partial and combined effect on Purchasing Decisions (Y). The results of the coefficient of determination (R2) test suggest a relationship between the variables Social Media Influencers (X1) and Café Atmosphere (X2) and Purchase Decisions (Y) at Café T1311 Medan. Café T1311 Medan is expected to continue utilizing Social Media Influencers (X1) as a promotional tool for the café and to sustain the café atmosphere (X2). This involves maintaining various aspects of café facilities, ensuring cleanliness, and periodically updating the café's interior design in alignment with emerging trends. These efforts aim to create a comfortable and enjoyable dining experience for consumers.